Clinical care for severe acute respiratory infection: toolkit: COVID-19 adaptation - Coelho Paraguassu, Éber; dos Passos Lacerda, Jamille; World Health Organization (Brazilian Journal of Implantology and Health Sciences, 2022)
This article is a sharing in the form of a literal copy of the original “Clinical Care for Severe Acute Respiratory Infection”: World Health Organization; 2022. CC BY-NC-SA 3.0 IGO License . This sharing aims to boost knowledge about this new disease called COVID 19. _____________________________________________________________________________________________________________________________________ A global case definition for severe acute respiratory infection (SARI) for surveillance purposes, applicable to all age groups, was first published by the World Health Organization (WHO) in 2011. The current WHO case definition is: Patients with acute respiratory infection who have history of fever (or measured fever of ≥ 38 °C), cough and onset within the last 10 days (symptoms within 10 days) and require hospitalization.